Post-transplant erythrocytosis refractory to ACE inhibitors and angiotensin receptor blockers - Vishnu, Prakash (BMJ Case Rep, 2018)
Post-transplant erythrocytosis (PTE) is a condition with elevated haematocrit (hct) in renal allograft recipients. The mainstay of treatment is ACE inhibitors (ACEi) or angiotensin II receptor blockers (ARB), but seldom phlebotomy. PTE must be recognised early to prevent major thromboembolic events. We present a case of PTE that was refractory to blockade of renin–angiotensin system (RAS) by ACEi and ARB and required phlebotomy for control of hct. Our review of medical literature about prevalence and pathophysiology of PTE suggests that approximately 22% of patients with PTE are refractory to ACEi/ARB treatment. There are four plausible pathways that appear to play a role in causing PTE: disruption of erythropoietin regulation, mitogenic effect of the RAS on erythroid lineage, insulin-like growth factor 1 and androgenic stimulation. Presently, there is no unifying hypothesis involving these factors, but refractoriness to ACEi/ARB may represent a distinct subcategory of PTE.